A Project- Based Approach to Enhance Skills in Science Investigatory Projects among Secondary School Students in Northern Mindanao - G. Gomez, Rizalina (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper investigated the use of a Project-Based Approach as a pedagogical tool to enhance students’ skills in conducting science investigatory projects. Two hundred fifty (250) students and ninety eight (98) science teachers in public secondary schools in Northern Mindanao, Philippines had accomplished questionnaires. Students’ engagement in Project Based Approach significantly increased their selfefficacy in conducting science investigatory projects and developed skills in collaborating, problem solving, and critical thinking. In the conduct of the investigatory projects, the students exhibited a greater understanding of science concepts and skills in quantitative analysis. The quality of the student researches was improved resulting in the inereased number of participation in Science fair competitions. performances in Science. Results showed that the students skills in conducting investigatory projects generally improved with increased exposure to this collaborative teaching tool. This study concluded with pedagogic implications for teachers to enhance their skills in the use of a Project-Based Approach and was recommended to sustain its use as an effective strategy in teaching.